The technology of thermal cyclic electrolytic plasma hardening of steels - Б.К. Рахадилов; Р.С. Кожанова; Ю.Н. Тюрин; Л.Г. Журерова; Ж.Б. Сагдолдина (Қарағанды университетінің хабаршысы. Физика сериясы)
This work describes the technology of thermal cyclic electrolytic plasma hardening, as well as describes the design features of the electrolytic plasma heater. There are presented the results of the research of medium-carbon steel hardness treated by thermal cyclic electrolytic plasma hardening under different conditions. An industrial installation for thermal cyclic electrolytic plasma hardening of materials was developed to carry out thermal cyclic electrolytic plasma hardening of steels in an automated mode. Tempered layers were obtained on the surface of the samples with average thickness values from 0.5 to 10 mm and hardness up to 750 HV. Experimentally that the alternation of switching on the electric potential at a voltage of U1 = 320 V and U2 = 200 V provides heating of the product surface to a depth of 10 mm. In this case, the maximum hardness of the surface layer (750 HV) practically does not depend on the thickness of the hardened layer. The hardness of the hardened layer of the product gradually decreases from the maximum (750 HV) to the hardness of the base (280-300 HV). The developed installation allows to vary the electrophysical parameters within a wide range: to set the voltage, the duration of processing, the time of switching on and off the voltage.